Gazeta Polska . pismo Konfederacji Polski Niepodległej, no. 43, 1988 - ed. committee (Warszawa, 1988)
Creation and circulation: After the introduction of the Martial Law, publication suspended in 1982-1985. Republished underground in 1986-1989. Republished again in 1992